A revisit on the characteristics of Yao-Cheng non-linear oscillator. Issue 1 (March 2023) - Rath, Biswanath; Nayak, Bibekananda; Mallick, Pravanjan; Sahoo, Rati Ranjan; Erturk, Vedat Suat; Wannan, Rania; Jarrar, Rabab; Shanak, Hussein; Asad, Jihad
We revisited the characteristic features of Yao-Cheng non-linear oscillator by employing both analytical as well as numerical approaches. Our study indicates that the solution of the non-linear oscillator shows oscillatory behaviour. Further, the phase portrait for this oscillator system reflects the closed loop signifying the stability of the system. Our results suggest the absence of damping in this physical system.